Triestine literature between Slovenia and Italy - Pizzi, Katia (Primerjalna književnost, 2013)
This article examines a body of literature between Slovenia and Italy in the early Twentieth century. This literature will emerge as particularly modern due to the paradigm of its regional peripherality. Srečko Kosovel and Scipio Slataper, however, were not to realize transcultural projects at the regional level, notwithstanding their pro-European agendas.
Keywords: Kosovel, Srečko, 1904-1926; Trst; Slataper, Scipio, 1888-1915; Slovene literature; slovenska književnost; italijanska književnost; literarno obrobje; kulturna identiteta; transkulturalizem; literarne študije